2016
DOI: 10.1515/popets-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

SoK: Privacy on Mobile Devices – It’s Complicated

Abstract: Modern mobile devices place a wide variety of sensors and services within the personal space of their users. As a result, these devices are capable of transparently monitoring many sensitive aspects of these users’ lives (e.g., location, health, or correspondences). Users typically trade access to this data for convenient applications and features, in many cases without a full appreciation of the nature and extent of the information that they are exposing to a variety of third parties. Nevertheless, studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 79 publications
0
22
0
1
Order By: Relevance
“…This problem can be observed for many smart city technologies, including the IoT, wearable devices, sensor networks, autonomous systems, and intelligent vehicles, especially when these devices support a wide range of protocols and include many software components. This is naturally the case for mobile phones that, when compromised, can lead to a complete violation of user privacy (see [170] and [64] for surveys on mobile phone security and privacy). The fact that users can actively download third-party software onto the devices furthermore opens up the problem of malware [171].…”
Section: No Privacy Without Securitymentioning
confidence: 99%
See 2 more Smart Citations
“…This problem can be observed for many smart city technologies, including the IoT, wearable devices, sensor networks, autonomous systems, and intelligent vehicles, especially when these devices support a wide range of protocols and include many software components. This is naturally the case for mobile phones that, when compromised, can lead to a complete violation of user privacy (see [170] and [64] for surveys on mobile phone security and privacy). The fact that users can actively download third-party software onto the devices furthermore opens up the problem of malware [171].…”
Section: No Privacy Without Securitymentioning
confidence: 99%
“…In addition, these devices consist of various components developed by different parties with different goals and incentives, which makes the protection of sensitive user data more difficult. As a result, existing privacy solutions often focus only on a small part of the mobile device ecosystem and thus leave the user vulnerable [64].…”
Section: A Ubiquitous Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Such concerns are grounded in concrete vulnerabilities of existing wearables, as shown in an extensive survey of consumer wearables [60] spanning from typical activity trackers to smart textile implants -albeit ignoring pet wearables or indeed any wearable not directly worn by a human. A systematization of knowledge on privacy on mobile devices by Spensky et al [62] found that many privacy related vulnerabilities arise due to the complexity of software ecosystems, as technologies to protect privacy tend to focus on small parts of the ecosystem, abstracting away from its entire complexity. Pu and Grossklags [54] investigated factors that influenced users' privacy concerns towards data of themselves and data of friends (e.g., through Facebook connections).…”
Section: Related Work 21 Pet Wearables and Privacy Concernsmentioning
confidence: 99%
“…In [163], the authors have shown that smart device privacy is complicated since it consists of different layers of hardware, operating system, and apps. Another layer of the sensor data mining process is added over this layered stack.…”
Section: 2mentioning
confidence: 99%